EXPLAINABLE ARTIFICIAL INTELLIGENCE THEORY IN DECISION MAKING TREATMENT OF ARITHMIA PATIENTS WITH USING DEEP LEARNING MODELS - Satoni Kurniawansyah, Arius (Yayasan Nuraini Ibrahim Mandiri, 2023)
In the context of Explainable Artificial Intelligence, there are two important keywords: interpretability and